INOVASI DAN KREATIVITAS DALAM PENDIDIKAN AGAMA ISLAM : INOVASI DAN KREATIVITAS DALAM PENDIDIKAN AGAMA ISLAM - Dewi Yuliyana (Marifah: Jurnal Pendidikan dan Pemikiran Peradaban Islam, 2026)
Innovation and creativity in Islamic religious education are important elements in improving the quality of learning and understanding of Islamic teachings. Along with the development of the times, Islamic religious learning must be able to adapt to social, technological, and cultural changes. Innovation in teaching methods, curriculum, and learning media is the key to achieving effective religious education goals. Creativity in designing teaching materials and a fun approach is also an important factor in attracting student interest and ensuring deep understanding. This article examines various forms of innovation and creativity applied in Islamic religious education, as well as their impact on the development of students' religious understanding. It is hoped that with innovation and creativity, Islamic religious education can be more relevant to the challenges of the times and be able to shape students' characters based on Islamic values ​​that are rahmatan lil-‘alamin. Keywords: Innovation, Creativity, Islamic Religious Education, Learning, Learning Media.